A Clean Swipe: Assessing the Vulnerability of South Africa and Nigeria to Money Laundering Committed with Prepaid Cards. Issue 1 (February 2023) - Nkoane, Paul
Abstract : Criminals use a myriad of measures to isolate their criminal spoils from the crime while lawmakers continuously adopt measures to plug the lacunae in the anti-laundering machinery. Thus, lawmakers are expected to constantly adjust the laws intended to limit money laundering, lest the battle against this criminal delinquency will be lost. This article is intended to highlight that money laundering in this era of progressive technology has become more elusive. The internet has fed new trends into the metamorphosis of money laundering, with New Payments Methods fuelling the fire. The use of electronic payments has unlocked new avenues for money laundering. This generally should be attended by the obvious task of improving AML/CFT machinery. The article intends to illustrate how other techniques that undermine the existing anti-money laundering machinery can be fashioned when prepaid cards are employed. The article assesses the South African, Nigerian and international anti-laundering regimes.